Analysis of the Role of Internal Audit in Enhancing Company's Internal Control - Syahputra, Rafli Muhammad (Manunggal Halim Jaya, 2022)
This research aims to investigate the role of blockchain technology in auditing processes, focusing on its implications, challenges, and opportunities. The study employs a qualitative approach, synthesizing existing literature, theoretical frameworks, empirical findings, and practical applications to gain comprehensive insights. Institutional theory and the Technology-Organization-Environment (TOE) framework provide theoretical foundations for understanding blockchain adoption dynamics. Empirical research highlights the effectiveness of blockchain-enabled auditing tools in enhancing transparency, reliability, and efficiency, albeit with challenges related to regulatory compliance, data privacy, and technological interoperability. Practical applications showcase blockchain's potential to revolutionize audit methodologies, automate procedures, and improve data integrity. Key findings indicate that blockchain adoption in auditing is influenced by institutional pressures, technological characteristics, organizational factors, and environmental dynamics. While blockchain offers opportunities for enhanced audit quality and assurance services, strategic implementation and collaboration are essential to address barriers and optimize benefits. This research contributes to the scholarly discourse on blockchain technology in auditing, informing future research directions and industry practices.